Association between anthropometric indicators of body fat and metabolic risk markers in post-menopausal women - Orsatti, Fabio Lera [UNESP]; Nahás, Eliana Aguiar Petri [UNESP]; Nahas-Neto, Jorge [UNESP]; Maesta, Nailza [UNESP]; Orsatti, Claudio Lera [UNESP]; Vespoli, Heloísa Maria de Luca [UNESP]; Traiman, Paulo [UNESP] (Informa Healthcare, 2010)
Objective. to evaluate anthropometric indicators of body fat and their association with metabolic risk markers in postmenopausal women.Methods. A cross-sectional study with 80 Brazilian women (40-70 years) was carried out. Body mass index (BMI = weight/height(2)), waist circumference (WC) and waist-to-hip ratio (WHR) were obtained for anthropometric evaluation. Trunk fat mass (TFM) was measured by dual-energy X-ray absorptiometry. The following metabolic variables were evaluated: total cholesterol (TC), HDL, LDL, triglycerides (TG), as well as glycemia and insulin to determine insulin resistance (HOMA-IR).Results. Overweight and obesity were observed in 81% of the women. Values of WC >88 cm were observed in 68.5% of the women. on average, TC, LDL and TG levels were above normal levels in 60, 50 and 42.5% of the women, respectively; and HDL was normal in 82.5%. IR was observed in 37.5% of the women. Positive correlations were found between anthropometric indicators and TFM (P < 0.05). WC was most correlated with TFM (r = 0.92), followed by BMI (r = 0.88) and by WHR (r = 0.48; P < 0.05). All anthropometric indicators and TFM showed significant negative correlations with HDL and significant positive correlations with HOMA-IR (P < 0.05). Only WHR was significantly associated with dysglycemia (R(2) = 12%), hypertriglyceridemia (R(2) = 17%) and decreased HDL (R(2) = 27%). WC was significantly associated with HOMA-IR (R(2) = 34%).Conclusion. WC and WHR are anthropometric measures that showed strong correlation with TFM and with metabolic risk markers in postmenopausal women.
Keywords: Menopause; dual-energy X-ray absorptometry; waist circumference; insulin resistance; metabolic risk